Tratamento do fenômeno de extravasamento/retenção de muco pela técnica de micro-marsupialização modificada associado ou não ao uso do laser de baixa intensidade: ensaio clínico controlado e randomizado - Marcio Bruno Figueiredo do Amaral (2011)
Objective: To investigate the ability of low-level-laser therapy (LLLT) to reduce recurrence rates and alleviate pain caused by the modified micro-marsupialization treatment of mucus extravasation or retention phenomena. Patients and Methods: Six patients with oral ranulas and selected mucoceles were submitted to micro-marsupialization treatment (control group) and eleven were submitted to micro-marsupialization treatment associated with LLLT (LLLT group). Laser irradiation of patients with the LLLT group was performed using a 100 mW 660 nm continuous wave Gallium Aluminum Arsenide (GaAlAs) laser. Irradiation was carried out immediately following the micro-marsupialization treatment and at 24, 48 and 72 hours post-micro-marsupialization treatment. A numeral rating scale and a visual analogue scale of faces were used to assess the pain. The relationship between the treated groups and pain was assessed using the Mann-Whitney test. Results: All treated oral ranulas and selected mucoceles had clinical healing and no evidence of recurrence during the mean 10.88-month follow-up period. It could be observed that the LLLT group reported less pain than did control group. Conclusion: LLLT is a good alternative to reduce post-surgical pain caused by micro-marsupialization treatment of mucus extravasation or retention phenomena.